2022
DOI: 10.1007/s00415-022-11004-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Specific Enolase, S100-beta protein and progranulin as diagnostic biomarkers of status epilepticus

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Certainly, this factor could have influenced our results and the discrepancies found with the previous studies. Associations between S100B and candidate genes for dyslexia have been reported [ 68 , 69 ]; in patients suffering from status epilepticus, significantly-increased levels of S100B were found in comparison with controls or patients with pharmacoresistant epilepsy [ 70 ]. Indeed, the administration of arundic acid (an S100B inhibitor) to murine models of epilepsy reduced neuroinflammation and improved astrocytic function after status epilepticus [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, this factor could have influenced our results and the discrepancies found with the previous studies. Associations between S100B and candidate genes for dyslexia have been reported [ 68 , 69 ]; in patients suffering from status epilepticus, significantly-increased levels of S100B were found in comparison with controls or patients with pharmacoresistant epilepsy [ 70 ]. Indeed, the administration of arundic acid (an S100B inhibitor) to murine models of epilepsy reduced neuroinflammation and improved astrocytic function after status epilepticus [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…La neurogranina es un biomarcador prometedor pero del que por el momento no se dispone de suficiente evidencia 41 . Otros como el S100B o incluso enolasa, han mostrado cierto valor en el diagnóstico de situaciones de EE 42 .…”
Section: Diagnóstico De La Ceunclassified
“…Besides, CSF progranulin was documented to be increased in epileptic patients following status epilepticus compared to control 120 . A cohort study on patients with resistance epilepsy ( n = 56) revealed that CSF progranulin level was increased compared to healthy subjects ( n = 36) 122 . Of note, metformin activates the expression of neuroprotective and anti‐inflammatory progranulin 123 .…”
Section: The Mechanistic Role Of Metformin In Epilepsymentioning
confidence: 99%